Nutrient availability and grazing influence the strength of priority effects in bacterial freshwater communities (data set) - Lumpi, Theresa (Uppsala University, 2023)
We conducted an experiment to investigate the importance of priority effects in bacterial communities with regard to nutrient availability and grazing.

In the course of the experiment, we measured nutrient availability as total phosphorus (TP) spectrophotometrically. Total nitrogen (TN), as well as total organic carbon (TOC) levels, were obtained by catalytic thermal decomposition method. The combined dataset shows the nutrient values for the original lakes, the sterile media used in the experiment as well as all experimental samples for both sampling occasions (day 10 and day 15).

Bacterial abundances were monitored using flow cytometry (FC) count data. The combined dataset includes bacterial count data from the pre-cultivation of the bacterial communities before the start of the experiment. Bacterial count data from the running experiment are included afterward.

Heterotrophic nanoflagellates (HNF) as the bacterial grazers were counted microscopically. The dataset shows HNF counts from grazing treatments in the experiment starting from day 3. On experimental days 3 and 10, additional non-grazing treatments were included to examine the potential presence of HNF.

When bacterial communities mix, immigration history can fundamentally affect the community composition as a result of priority effects. Priority effects arise when an early immigrant exhausts resources and/or alters habitat conditions, thereby influencing the establishment success of the late arriver. The strength of priority effects is context dependent and expected to be stronger if environmental conditions favor the growth of the first arriver. In this study we conducted a two-factorial experiment testing the importance of nutrient availability and grazing on the strength of priority effects in complex aquatic bacterial communities. We did so by mixing two dissimilar communities, simultaneously, and with a 38 hours’ time-delay. Priority effects were measured as the invasion resistance of the first community to the invading second community. We found stronger priority effects in treatments with high nutrient availability and in absence of grazing, but in general the arrival timing was less important than the selection by nutrients and grazing. At the population level, the results were complex, but priority effects may have been driven by bacteria belonging to for example the genera Rhodoferax and Herbaspirillum. Our study highlights the importance of arrival timing in complex bacterial communities especially in environmental conditions which favor rapid community growth.

The dataset was originally published in DiVA and moved to SND in 2024.
Nutrient availability and grazing influence the strength of priority effects in bacterial freshwater communities (data set)
Keywords: priority effects; priority effects; bacterial communities; bacterial communities; nutrient availability; nutrient availability; grazing; grazing; Ecology; Ekologi